ETIKA DAN HUKUM DALAM PENGGUNAAN HAK CIPTA DI MEDIA SOSIAL - Sulasno Sulasno; Fitria Agustin Fitria Agustin (LPPM STIA Banten, 2018)
The birth of the internet in a human interaction system raises the complexity of legal issues that must be applied. One of the complexities in the law also covers the legal protection of copyright in the internet media. The problems that arise then are not the only things that are related to the law but no less important are ethics, values ​​and morals. The Internet has caused new problems in the field of Intellectual Property Rights (HAKI). Copyright, trademark, patent, trade secret, and moral rights are severely affected by the Internet. The Internet has several technical characteristics that make the intellectual property problems thrive. The research method in this paper is a qualitative research with analytical descriptive approach that is a normative juridical approach through legislative approach, conceptual approach and case approach and comparative approach in order to obtain and find objective truth. The purpose of this research is to analyze and know the position of ethics and law on the use of copyright in social media. To analyze Legal Protection against Copyright Infringement in Social Media. Copyright law is a legal provision that provides protection for the results of humans intellectual creations in art, literature, and science. Copyright law itself gives exclusive rights of being automatic when a work in art, literature and science is manifestly realized.